IMPACT OF AGE ON OUTCOME OF COVID-19 PATIENTS AT A TERTIARY CARE HOSPITAL - Rafique, Iffat; Yasir, Muhammad; Zia, Nadeem; Sheen, Irfan Najm; Siddiqui, Hamid Jamal; Nadeem, Asif (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the impact of age on outcome of COVID-19 patients at a tertiary care hospital. Study Design: Cross sectional study. Place and Duration of Study: Combined Military Hospital Malir, Karachi, from Apr to Jun 2020. Methodology: This was a retrospective cross sectional study conducted at Combined Military Hospital Malir Karachi. About 120 positive cases of SARS COV-2 were studied, including males and females. Age range was 21-85 years. Patients were divided into groups according to age, group A (21-40 years), group B (41-55 years), group C (56-85 years). Presenting complaints and associated co morbidities were also analyzed. Mild cases were managed conservatively. Moderate to severe oxygen dependent cases were managed in intensive care units. Results: The mean age of patients was 40.24 years with 16.25 ± SD. Co- morbidities were noted in 67 (55.83%) patients, highest in group C, hypertension being the most common. Ten patients could not survive, due respiratory failure complicated by adult respiratory distress syndrome (ARDS). Bilateral infiltrates >50% observed in (14%) out of (n=120) patients. One hundred and ten patients were discharged with uneventful recovery. Conclusion: Mortality was highest among elderly patients with comorbidities. Therefore, international standing operative measures (SOPs) to be followed. Meticulous monitoring of vital signs and oxygen saturation in mild cases is the bare minimum requirement and timely appropriate treatment escalation of moderate to severe cases in intensive care units is the key to success.